1983
DOI: 10.1128/aac.23.3.374
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of beta-lactam antibiotics and antineoplastic agents

Abstract: The in vitro interactions of four 1-lactam antibiotics and five antineoplastic agents were examined with 100 clinically isolated strains of four species of gramnegative bacilli. Generally, by the checkerboard dilution method, 3-lactam antibiotics, when tested in combination with mitomycin C, bleomycin, or 5-fluorouracil, showed synergistic action, whereas when tested in combination with carboquone, they showed antagonistic action. Almost no combinations of adriamycin showed the interactions. Among 3-lactam ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Synergy between 5-FU and cephalosporins has been noticed against gram-negative bacteria in studies using the checkerboard dilution method and determinations of fractional inhibitory concentrations [23,24]. In the present study, ceftazidime showed an indifferent bactericidal effect in combination with the tested antineoplastic agents.…”
Section: Discussionmentioning
confidence: 63%
“…Synergy between 5-FU and cephalosporins has been noticed against gram-negative bacteria in studies using the checkerboard dilution method and determinations of fractional inhibitory concentrations [23,24]. In the present study, ceftazidime showed an indifferent bactericidal effect in combination with the tested antineoplastic agents.…”
Section: Discussionmentioning
confidence: 63%
“…Changes in the composition of the oral micro-organisms have been reported for chemotherapy treatment in human studies (Lucas et al, 1997;Napeñas et al, 2010) and for 5-FU specifically in a rat study (Von BĂŒltzingslöwen et al, 2003), with a shift towards more Gram-negative rods and bacterial translocation to cervical and mesenteric lymph nodes following treatment with 5-FU. A number of studies have been looking at the antibacterial effect of 5-FU on monocultures of mainly pathogenic strains such as Pseudomonas, Klebsiella and Staphylococcus (Wright & Matsen, 1980;Ueda et al, 1983;Bodet et al, 1985;Takahata et al, 1986). Although 5-FU was shown to have substantial antibacterial effects, the tested concentrations in these studies were much higher than what is usually present in vivo.…”
Section: Introductionmentioning
confidence: 90%
“…Treatment with bleomycin, an antibiotic used against gramnegative bacteria (55) and with chemotherapeutic properties (5,27), leads to pulmonary fibrosis in Ïł18% of patients (40,47). Therefore, bleomycin has become the primary substance used to model pulmonary fibrosis in small rodents (36,37,46).…”
mentioning
confidence: 99%